Uang Dan Sistem Keuangan - Irma Yunita; Galuh Sabila; Elha Fawwa D.M; Agus Eko Sujianto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Something that is generally accepted to pay debts, buy goods and services, and pay for general needs is called money. However, a financial system is a collection of financial markets, financial service institutions, and financial infrastructure, including payment systems. They work together to facilitate the collection and allocation of funds to support national economic activities, as well as to companies and households connected to financial services institutions. How the monetary sector influences the stability of the Indonesian financial system is the subject of this research. with the problem formulation: 1) Understanding the function of money and, 2) Australian financial system, 3) Money circulation, 4) Money demand, and 5) Balance. The findings show that exchange rates, exchange rates and inflation can influence the stability of the financial system. The literature method was used in this research, which includes library research and secondary data obtained from the Indonesian Statistics Center. The results are very important for explaining how financial system stability is influenced by the monetary sector and how financial system stability affects Indonesia's economic growth.